Pengaruh Promosi Word of Mouth, Brand Image, dan Brand Ambassador Terhadap Keputusan Pembelian Skincare Azarine di Stuffbyms Kota Semarang - Regita Amalia Putri Sulistyo; Mulyo Budi Setiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The skincare industry in Indonesia is growing rapidly, with increasing competition between local and international manufacturers. This study aims to analyse the effect of Word of Mouth Promotion, Brand Image, and Brand Ambassador on purchasing decisions for Azarine skincare products at Stuffbyms Semarang City. Quantitative methods are used with questionnaires distributed to 83 respondents. The F test results show that the three independent variables simultaneously have a significant effect on purchasing decisions. The t test shows that Word of Mouth Promotion, Brand Image, and Brand Ambassador each have a positive and significant influence on purchasing decisions with a significance value of each below 0.05. The coefficient of determination (Adjusted R²) of 0.691 indicates that 69.1% of the variation in purchasing decisions can be explained by these variables. These findings provide important insights for Azarine's marketing strategy in the face of beauty industry competition.